The strategic designer : tools and techniques for managing the design process - Holston, David (HOW Books, 2011)
How do designers deal with the increasing complexity of design problems? What skills do designers need to be competitive in the future? This title shows designers how to build strong client relationships, elevate their standing with clients, increase project success rates, boost efficiency and enhance their creativity